The Influence of AI Literacy on the Intention to Use Generative AI in Learning: The Mediating Role of Perceived Usefulness and Moderating AI Anxiety - Zainal Syahlan; Leli Setyaningrum; Isnadi; Hadi Mardiyanto (Information Technology Education Journal, 2026)
Purpose – This study aims to examine the influence of AI Literacy on students’ Intention to Use Generative AI in learning activities through the mediating role of Perceived Usefulness and the moderating role of AI Anxiety within the higher education context. Design/methods/approach – The study employed a quantitative explanatory approach using a cross-sectional survey design. Data were collected from 250 university students who had prior experience using generative AI for academic purposes. Respondents were selected through purposive sampling based on predefined inclusion criteria. The research instrument consisted of structured questionnaire items measured using a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate the measurement model, structural relationships, mediation effect, and moderation effect among variables. Findings – The results indicate that AI Literacy significantly influences both Perceived Usefulness and Intention to Use Generative AI. Perceived Usefulness was also found to positively affect behavioral intention and partially mediate the relationship between AI Literacy and Intention to Use. Furthermore, AI Anxiety negatively moderated the relationship between Perceived Usefulness and Intention to Use, suggesting that psychological concerns toward AI weaken students’ willingness to adopt generative AI despite recognizing its educational benefits. Research implications/limitations – This study contributes to the development of AI-based technology acceptance research by integrating cognitive and psychological factors into a single analytical framework. However, the use of a cross-sectional design and self-reported data may limit the generalizability and causal interpretation of the findings. Originality/value – The originality of this study lies in the integration of AI Literacy, Perceived Usefulness, and AI Anxiety within the Technology Acceptance Model to explain generative AI adoption behavior in higher education learning environments.